The Effect of Budgetary Participation and Organizational Culture on Managerial Performance with Work Motivation as a Moderating Variable - Alfonsa Hildegardis Kin; Dyah Ani Pangastuti; Maxion Sumtaky (Jurnal Akuntansi dan Perpajakan, 2023)
This study aims to examine the effect of budgetary participation and organizational culture on managerial performance with work motivation as a moderating variable. This research is a quantitative study that tests the hypothesis: the effect of budgetary participation on managerial performance, the influence of organizational culture on managerial performance, tests the hypothesis of the relationship between budgetary participation and managerial performance with work motivation as a moderating variable and tests the hypothesis of the relationship between organizational culture and managerial performance, work motivation as moderating variable. The data used is primary data collected through a questionnaire survey. This study used a sample of 70 respondents from the Malacca district government office. Data analysis used multiple linear regression analysis and interaction test or moderation regression analysis (MRA). The results of the study show that budgetary participation has a significant positive effect on managerial performance. Organizational culture has a significant positive effect on managerial performance. The results also show that work motivation moderates the relationship between budgetary participation and managerial performance and work motivation moderates the relationship between organizational culture and managerial performance.